STUDYING STEEL-RECYCLED AGGREGATE CONCRETE BOND–SLIP BEHAVIOR USING DIGITAL IMAGE CORRELATION - OUDEH, YAZAN; DANHASH, GHOSON; DIAB, WASFI; WARDEH, GEORGE (Journal of Duhok University, 2023)
The present study has two points of interest, the first point is steel-recycled aggregate concrete bond behavior, and the second point is the reliability of digital image correlation in tracking experimental deformations. Recycled aggregate concrete exhibits lower mechanical properties than natural aggregate concrete, as international standards were designed for natural aggregate concrete, so their applicability to recycled aggregate concrete is still ambiguous. In this study, five mixes were designed to verify the steel-recycle aggregate concrete internal bond-slip behavior, for five different replacement ratios (0%, 25%, 50%, 75%, and 100%), the test was supported by the DIC technique for getting the slip, adding to LVDT for verifying the results. The GOM program can analyze the test video, but this takes a lot of time. For getting the steel slip using the GOM program, a series of frames were extracted from the test video via the VLC media player program, and converted to black and white colors using the XnViewMP program to be analyzed in the 2D GOM program. The steel-recycled aggregate concrete bond-slip curves obtained from the Digital Image Correlation (DIC) technique using the 2D GOM program were comparable with those obtained from LVDT, which means that the DIC technique is a reliable method for tracking experimental deformations.The experimental results showed that the compressive strength decreased when the replacement ratio increased, where the decrease was 7.6%, 6.6%, 9.3%, and 13% for replacement ratios of 25%, 50%, 75%, and 100%. Bond strength decreased when the replacement ratio increased, where the decrease was 23.7%, 25.7%, 30.5%, 34.9% for replacement ratios 25%, 50%, 75%, 100%. There was no clear relationship between the slip and replacement ratio. A comparison with the international standards for bond-slip curves showed that the model of Harajli gives close results for steel–recycled aggregate concrete.